Secukinumab Reduces Psoriasis-associated Pruritus and Regenerates the Cutaneous Nerve Architecture: Results from PSORITUS a Doubleblind, Placebo-controlled, Randomized Withdrawal Phase IIIb Study - Lina Renkhold; Manuel P. Pereira; Karin Loser; Dieter Metze; Daniel Baeumer; Nima Melzer; Maximilian Reinhardt; Athanasios Tsianakas; Thomas Luger; Christian Mess; Ruth Becker; Clara Hambüchen; et al. (Acta Dermato-Venereologica)
The occurrence of pruritus in psoriasis was previously underestimated but is a significant burden. Secukinumab (SEC), a monoclonal anti-interleukin-17A antibody, efficiently controls signs of psoriasis, but the effect on pruritus and cutaneous neuroanatomy remained unknown. The primary objective of this study (NCT02362789) was to evaluate the superiority of SEC treatment vs placebo on pruritus intensity (visual analogue scale; VAS). Furthermore, the treatment-dependent course of pruritus in association with absolute Psoriasis Area Severity Index (PASI) score, as well as cutaneous histopathology and neuroanatomy, was assessed. Open-label SEC 300 mg s.c. was administered regularly until week 16. Patients who reached a ≥ 98% PASI reduction (PASI ≥ 98) were randomized to receive either placebo or SEC up to week 32. Punch biopsies were collected from lesional psoriatic (baseline, weeks 16 and 32) and non-lesional (baseline) skin for histopathological and neuroanatomical analyses. VAS scores improved significantly after open-label SEC treatment but relapsed upon placebo (29.92 ± 33.8) compared with SEC (12.30 ± 22.6; p = 0.036). After SEC-dependent improvement in PASI, histopathology, marker expression and neuroanatomy, relapse was observed with treatment discontinuation in all parameters except neuroanatomy. SEC was superior to placebo by efficiently controlling reduced pruritus intensity, clinically normalizing skin lesions, and reversing histopathological abnormalities. The neuroanatomy recovered upon SEC and remained stable even after withdrawal.